1999
DOI: 10.1016/s0945-053x(99)00008-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of coding sequences for tissue inhibitor of metalloproteinases 1 (TIMP1) and 2 (TIMP2) in patients with aneurysms

Abstract: Aneurysms are characterized by dilation, i.e. expansion and thinning of all the arterial wall layers, which is accompanied by remodeling of the connective tissue. Genes involved in the regulation of tissue remodeling are therefore candidate genes. We analyzed TIMP1 and TIMP2 coding sequences in 12 individuals with abdominal aortic aneurysms (AAA), one individual with AAA and intracranial aneurysms (IA), four individuals with IA and two clinically unaffected individuals. We identified two nucleotide variants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 13 publications
2
31
0
1
Order By: Relevance
“…Furthermore, polymorphisms in the MMP-3 promoter and the gene for TIMP-1, but not the gene for MMP-9, have been reported to be associated with abdominal aortic aneurysm (39,42). A few patients in our KD study population had extremely high pro-MMP-9 enzyme or pro-MMP-9 protein levels.…”
Section: Vol 10 2003 Elevated Pro-mmp-9 and Timp-1 In Kd 311mentioning
confidence: 77%
“…Furthermore, polymorphisms in the MMP-3 promoter and the gene for TIMP-1, but not the gene for MMP-9, have been reported to be associated with abdominal aortic aneurysm (39,42). A few patients in our KD study population had extremely high pro-MMP-9 enzyme or pro-MMP-9 protein levels.…”
Section: Vol 10 2003 Elevated Pro-mmp-9 and Timp-1 In Kd 311mentioning
confidence: 77%
“…Wang et al 38 have analyzed the sequences of the TIMP-1 and TIMP-2 genes in a mixed North American and European white population with abdominal aortic aneurysm, but also in 1 individual with both aortic and intracranial aneurysms and 4 individuals with intracranial aneurysms. They identified 2 polymorphisms each in TIMP-1 and TIMP-2 and presented preliminary results of different allele frequencies of a nucleotide 573 polymorphism in the TIMP-2 gene between male controls and patients with abdominal aortic aneurysms.…”
Section: Krex Et Al Timp Polymorphisms In Aneurysm Patientsmentioning
confidence: 99%
“…A relative decrease in TIMP expression has been found in aneurysmal aortas. Although this study concluded that this deficiency was not a result of a primary gene mutation (Tilson et al, 1993), more recent studies have identified both a TIMP-1 and TIMP-2 polymorphism to be expressed in higher frequencies in patients with AAA (Ogata et al, 2005;Wang et al 1999). Despite this, the observed single base pair change does not change translation and is therefore unlikely to be involved in the pathogenesis of AAA.…”
Section: Tissue Inhibitors Of Mmp's and Plasminogen Activator Inhibitorsmentioning
confidence: 66%